FAKTOR-FAKTOR YANG MEMPENGARUHI JUMLAH BANTUAN PEMERINTAH PUSAT DI LIMA KABUPATEN / KOTA 222 DI JAWA TENGAH - Sri Nawatmi (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2006)
Otonomy expected to region empowerment increase, so aid from central government decrease. Thus, the state budgets burden can decrease. Unfortunatly, no every region ready to otonomy. Because of that, it’s important to research about what’s the determinant of the aid from central government to regions. The object is Jawa Tengah, especially Boyolali, Klaten, Sukoharjo, Surakarta and Wonogiri. This paper present research with data pooling. The model estimated with GLS (Generalized Least Square) method. The research produced : The correct model is FEM (Fixed Effect Model). The significant variable is PDRB (positif), own source revenue (negative) and numbers of people (negative). The best aid accepted by Klaten and Surakarta at least if value of independent variables is nol.Keywords : Data pooling, GLS, FEM, REM,Common model